Hydraulics for civil engineers - Wynn, Peter (London, United Kingdom : ICE Publishing, 2014)
Hydraulics for Civil Engineers provides a fundamental introduction to the area of fluid mechanics and hydraulics. This book covers all key areas of learning including such subjects as hydrostatics; hydrodynamics; turbines and pumps; flow and waves.
Contents Pressure in liquids: its effects and measurement -- Conservation equations applied to flow to liquid in pipes -- Real flow in pipes -- Turbines and pumps -- Steady uniform flow in open channels -- Open channel flow with varying conditions -- Hydrology of river flow -- Hydrology of surface water drainage -- Coastal hydraulics -- Dimensional analysis -- Two-dimensional ideal flow.
Includes bibliographical references.
Keywords: HYDRAULIC ENGINEERING